A mother's work : how feminism, the market, and policy shape family life - Gilbert, Neil, 1940- (Yale University Press, 2008)
"The question of how best to combine work and family life has led to lively debates in recent years. Both a lifestyle and a policy issue, it has been addressed psychologically, socially, and economically, and conclusions have been hotly contested. But as Neil Gilbert shows in this penetrating and provocative book, we haven't looked closely enough at how and why these questions are framed, or who benefits from the proposed answers." "A Mother's Work takes a hard look at the unprecedented rise in childlessness that, along with the outsourcing of family care and household production, has helped to alter family life since the 1960s. It challenges the conventional view on how to balance motherhood and employment, and examines how the choices women make are influenced by the culture of capitalism, feminist expectations, and the social policies of the welfare state. Gilbert argues that while the market ignores the essential value of a mother's work, prevailing norms about the social benefits of work have been overvalued by elites whose opportunities and circumstances little resemble those of most working- and middle-class mothers. And the policies that have been crafted too often seem friendlier to the market than to the family. Gilbert ends his discussion by looking at the issue internationally, and he makes the case for reframing the debate to include a wider range of social values and public benefits that present more options for managing work and family responsibilities."--Jacket